1986
DOI: 10.1530/acta.0.1120329
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone in panhypopitutarism: dynamic studies and therapeutic effects in Sheehan's syndrome

Abstract: To appreciate the aldosterone secretion status in panhypopituitarism, the steroid response to stimulation was studied in a homogeneous group of 20 female patients presenting with global hypopituitarism. Specific effects of glucocorticoid and thyroid hormone deficiencies were also assessed by studying the same patients before and after cortisol (F) and cortisol plus thyroid hormone (F + T) substitution. The patients were submitted to two stimulation tests before and after each treatment: the orthostasis test (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Although the diagnosis of primary aldoste¬ ronism was not confirmed by surgery and histological findings, long-standing hypokalemia, hyperaldosteronism, which was not suppressed by high salt loading or captopril, and hyporeninemia even under the extreme stimulation by low salt diet with furosemide administration and upright exercise, strongly suggested autonomous secretion of aldosterone. Elevated plasma aldosterone con¬ centration was characteristic of this patient, since it has been reported that basal plasma aldosterone concentration and its response to various stimula¬ tions are blunted in hypopituitarism (4,5). Low plasma aldosterone concentration is also reported in hypothyroidism alone (6).…”
Section: Discussionsupporting
confidence: 53%
“…Although the diagnosis of primary aldoste¬ ronism was not confirmed by surgery and histological findings, long-standing hypokalemia, hyperaldosteronism, which was not suppressed by high salt loading or captopril, and hyporeninemia even under the extreme stimulation by low salt diet with furosemide administration and upright exercise, strongly suggested autonomous secretion of aldosterone. Elevated plasma aldosterone con¬ centration was characteristic of this patient, since it has been reported that basal plasma aldosterone concentration and its response to various stimula¬ tions are blunted in hypopituitarism (4,5). Low plasma aldosterone concentration is also reported in hypothyroidism alone (6).…”
Section: Discussionsupporting
confidence: 53%
“…The status of the renin-angiotensin-aldosterone sys tem in pituitary insufficiency is still controversial [8,9]. Although a few studies have been reported, the system seems to be maintained adequately in the isolated ACTH deficiency syndrome [1], Only a single case of hyporeninemic hypoaldosteronism associated with this syndrome has been reported.…”
Section: Discussionmentioning
confidence: 99%